Making a noise! Aboriginal perspectives on art, art history, critical writing and community - Ash-Milby, Kathleen; Bouchard, Marie; Cardinal-Schubert, Joane; Collison, Nika; Collison, Vincent; Croft, Brenda L.; Durand, Guy Sioui; Hill, Richard; Hopkins, Candice; Logan, Jim; Martin, Lee-Ann; Mattes, Catherine; et al. (Banff : Banff International Curatorial Institute Banff Walter Phillips Gallery - The Banff Centre for the Arts Banff, 2004)
Begay, Shonto ; Bell, Richard ; Bourgault, Pierre ; Dupuis, Raymond ; Fontaine, Christopher ; Hutchinson, Lonnie ; Newashish, Jacques ; Pardington, Fiona ; Pohio, Nathan ; Rakena, Rachael ; Robertson, Sonia ; Tuu'luuq, Marion
Biog. auteurs p. 232-238
Engels
boek
Keywords: Canada